Dynamic changes of Ct values of N gene and ORF1ab genes and laboratory parameters in patients with COVID-19 caused by SARS-CoV-2 B.1, BA.2, and BA.5 variants and their correlation with clinical characteristics - Yang, Wenjing; Chen, Taoran; Zhou, Qi; Xu, Jiancheng (Frontiers in Microbiology, 2025)
ObjectiveTo characterize the dynamic patterns of ORF1ab and N gene Ct values in oropharyngeal swabs from COVID-19 patients infected with different SARS-CoV-2 variants and assess their clinical and laboratory correlations.MethodsWe conducted a retrospective cohort study of 259 COVID-19 patients hospitalized in Jilin Province between 2021–2023. Comparative analyses were performed on: (1) variant-specific Ct value trajectories for ORF1ab and N genes, (2) nucleic acid conversion times, and (3) longitudinal hematological and biochemical parameters.ResultsB.1 variant exhibited the lowest median Ct values (ORF1ab: 31.37; N gene: 30.49) and longest median nucleic acid conversion time (18 days). BA.2 variant demonstrated the highest median Ct values (ORF1ab: 33.00; N gene: 32.00) and shortest conversion time (14 days). Disease progression correlated with: increased creatinine (CREA), neutrophil percentage (NE%), and coagulation markers (D-dimer). Decreased lymphocyte percentage (LY%).ConclusionSignificant inter-variant differences were observed in viral clearance kinetics (Ct values and conversion times) and organ dysfunction markers. These findings highlight variant-specific pathophysiological profiles, with B.1 showing prolonged viral shedding and Omicron subvariants (particularly BA.2) exhibiting faster clearance but distinct hematological perturbations.